TINJAUAN YURIDIS PERLINDUNGAN HUKUM TERKAIT TENAGA KERJA PEREMPUAN ATAS HAK CUTI HAID DALAM PERJANJIAN KERJA BERSAMA (PKB) DI PT. NIKOMAS GEMILANG BERDASARKAN UNDANG-UNDANG NOMOR 6 TAHUN 2023 TENTANG CIPTA KERJA - Irwan Sapta Putra; Mohammad Hifni; Analisa BR Gurusinga (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2026)
Legal protection for the right to menstrual leave is part of the fulfillment of the normative rights of female workers guaranteed in Article 81 of Law Number 13 of 2003 concerning Manpower. Although normatively, this right has received legal recognition, its implementation in industrial relations still faces various obstacles, such as a productivity-oriented work culture, low legal awareness of workers, ineffective administrative procedures, and workers' concerns about performance appraisals when using the right to menstrual leave. These conditions indicate a gap between legal regulations and their implementation in practice, so that a legal study is needed regarding the regulation and protection of civil law for the implementation of the right to menstrual leave for female workers at PT Nikomas Gemilang. The formulation of the problem in this research includes: (1) how the regulation of menstrual leave rights for female workers in employment relations is reviewed based on Law Number 13 of 2003 concerning Employment and the principles of civil law in employment agreements; and (2) how is the civil law protection for female workers regarding the implementation of menstrual leave rights in employment relations between workers and employers at PT Nikomas Gemilang. This study employed an empirical legal research method with an empirical juridical approach. Data were obtained through a literature review of laws and regulations, books, and scientific articles, as well as field research through interviews with the Management of PSP-SPN PT Nikomas Gemilang as resource persons. All data were analyzed qualitatively using a descriptive-analytical approach to obtain an overview of the effectiveness of legal protection for the implementation of menstrual leave rights. The results of the study indicate that the regulation of menstrual leave rights has a strong legal basis based on Article 81 of Law Number 13 of 2003 concerning Manpower and Law Number 6 of 2023 has been implemented in the Collective Labor Agreement (PKB) of PT Nikomas Gemilang as part of the reproductive rights of female workers. Viewed from a civil law perspective, these regulations reflect the application of the principle of freedom of contract limited by law, the principle of pacta sunt servanda, and the principle of good faith. However, the effectiveness of legal protection is still influenced by legal culture factors, implementation procedures, and the level of legal awareness of the parties. Therefore, it is necessary to strengthen implementation through simplification of procedures for implementing menstrual leave rights, increased supervision by companies and trade unions, and ongoing socialization regarding the reproductive rights of female workers to achieve legal certainty, justice, and benefits in industrial relations.